1967
DOI: 10.1042/bj1020742
|View full text |Cite
|
Sign up to set email alerts
|

Liberation of surface-located penicillinase from Staphylococcus aureus

Abstract: 1. Growth of Staphylococcus aureus (8325; alphai(-)p(+)), constitutive for the production of penicillinase, in CY medium results in about 40% of the enzyme being free in the medium. By modifying the medium, 98% of the enzyme remains cell-bound. 2. Part of this is bound ionically to the surface of the cell wall and may be liberated instantaneously by certain inorganic anions. Maximum liberation was achieved with either phosphate or arsenate, both of which showed marked pH-dependence. 3. Polyanions that do not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Polyanions such as dextran sulfate have been shown to inhibit the formation and liberation of extracellular proteins including penicillinase (3,19) in whole cells of S. aureus, and it was suggested that the action of the polyanion was due to competition for sites on the cell wall. It was therefore of interest to determine the effect of polyanions on the synthesis and release of penicillinase in protoplasts of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyanions such as dextran sulfate have been shown to inhibit the formation and liberation of extracellular proteins including penicillinase (3,19) in whole cells of S. aureus, and it was suggested that the action of the polyanion was due to competition for sites on the cell wall. It was therefore of interest to determine the effect of polyanions on the synthesis and release of penicillinase in protoplasts of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies of the synthesis and liberation of penicillinase (EC 3.5.2.6) by cells of Staphylococcus aureus (3,4), we showed that there is a fraction of cell-bound penicillinase, comprising up to 40% of the total, which can be liberated by incubation of the cells for short periods at 37 C in 0.15 M sodium citrate. This fraction of cell-bound exopenicillinase is replenished only under conditions permitting de novo penicillinase synthesis and is the most recently synthesized enzyme (5).…”
mentioning
confidence: 91%
“…ated 3-lactamases have been described previously (22), even the location of the extracellular portion varies according to the medium in which the strain is grown. Coles and Gross have shown with strain PC1 that the proportion of staphylococcal ,-lactamase present in the supernatant of broth medium is much greater when the medium is buffered with phosphate (40% exoenzyme) than when it is buffered with Tris hydrochloride (<2% exoenzyme) (6). Presumably, in Tris the extracellular ,B-lactamase is ionically or hydrophobically bound to cell wall structures (6), whereas the P-lactamase is soluble in phosphate buffer and is displaced from the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Coles and Gross have shown with strain PC1 that the proportion of staphylococcal ,-lactamase present in the supernatant of broth medium is much greater when the medium is buffered with phosphate (40% exoenzyme) than when it is buffered with Tris hydrochloride (<2% exoenzyme) (6). Presumably, in Tris the extracellular ,B-lactamase is ionically or hydrophobically bound to cell wall structures (6), whereas the P-lactamase is soluble in phosphate buffer and is displaced from the cell. The possibility that extracellular staphylococcal P-lactamase normally adheres to cell wall structures and therefore is concentrated close to the bacterium that produced it is teleologically attractive, since it produces a situation similar to that observed with gram-negative bacteria, in which ,-lactamase is restricted to the periplasmic space by its inability to pass through the outer membrane (29,35).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of extracellular enzyme depends on the strain studied and on the conditions of growth (2). The majority of penicillin-resistant strains causing nosocomial infections are known to produce large amounts of extracellular 3-lactamase (4).…”
mentioning
confidence: 99%